The Relationship Between Patience and Personality Traits of Prospective Teachers Going to an Internship at the Faculty of Sports Sciences - Çankaya, Cemali; Dalbudak, İbrahim (Cadernos de Educação Tecnologia e Sociedade, 2024)
In this study, it was aimed to examine the relationship between patience and personality traits of prospective teachers going to internship at the faculty of sports sciences.In this study, a descriptive (survey) research model based on quantitative observation was used. The sample of the study consisted of 294 teacher candidates who go to internship in different faculties in Turkey. The "Teacher Patience Scale" developed by Meriç and Erdem (2022) was used to measure the differentiation of teacher candidates participating in the study on patience, and the "Ten-item Personality Scale" developed by Gosling et al. (2003) and adapted to Turkish by Atak (2013) was used to determine their personality traits. In the analyses; the differences between the groups were tested with the "Mann-Whitney U test" and "Kruskal-Wallis one-way analysis of variance (K-W ANOVA)" tests, and which groups cause the differences were tested with the "Dunn Bonferroni" test. As a result of the research, there is no significant relationship between the overall scale mean scores of teachers’ patience status and personality traits (p>0.05). There is a statistically significant and inversely strong relationship between teachers’ patience status and "Emotional stability" sub-factor total scores (p<0.05). There is no significant relationship between the mean scores of teachers’ patience status and the mean scores of other sub-factors of personality traits (p>0.05). There is no significant relationship between the mean scores of the general scale of personality traits and the mean scores of the sub-factors of teachers’ patience status (p>0.05). Considering the relationships between teachers’ patience status and sub-factors of personality traits, two significant relationships stand out (p<0.05). There is a statistically significant inverse and strong relationship between the mean scores of the sub-factors of "Teaching" and "Agreeableness", as well as "Interaction" and "Emotional stability". As a result, it was concluded that there was no significant relationship between teachers’ patience status and personality traits and the mean scores of other sub-factors.